Anti-Interleukin-1 Beta/Tumor Necrosis Factor-Alpha IgY Antibodies Reduce Pathological Allergic Responses in Guinea Pigs with Allergic Rhinitis - Hu Wei-xu; Zhou Wen-yun; Zhu Xi-ling; Wen Zhu; Wu Li-hua; Wu Xiao-mu; Wei Hui-ping; Wang Wen-ding; He Dan; Xiang Qin; Hu Guo-zhu (Mediators of Inflammation)
This study aims to determine whether the combined blockade of IL-1β and TNF-α can alleviate the pathological allergic inflammatory reaction in the nasal mucosa and lung tissues in allergic rhinitis (AR) guinea pigs. Healthy guinea pigs treated with saline were used as the healthy controls. The AR guinea pigs were randomly divided into (1) the AR model group treated with intranasal saline; (2) the 0.1% nonspecific IgY treatment group; (3) the 0.1% anti-TNF-α IgY treatment group; (4) the 0.1% anti-IL-1β IgY treatment group; (5) the 0.1% combined anti-IL-1β and TNF-α IgY treatment group; and (6) the fluticasone propionate treatment group. The inflammatory cells were evaluated using Wright’s staining. Histopathology was examined using hematoxylin-eosin staining. The results showed that the number of eosinophils was significantly decreased in the peripheral blood, nasal lavage fluid, and bronchoalveolar lavage fluid (P<0.05), and eosinophil, neutrophil, and lymphocyte infiltration and edema were significantly reduced or absent in the nasal mucosa and lung tissues (P<0.05) in the combined 0.1% anti-IL-1β- and TNF-α IgY-treated guinea pigs. The data suggest that topical blockade of IL-1β and TNF-α could reduce pathological allergic inflammation in the nasal mucosa and lung tissues in AR guinea pigs.